This Transient Life - Jissoji, Akio; Inagaki, Yuzo; Nakabori, Masao; Oneda, Kazumi; Tsukasa, Michiko; Tamura, Ryô; Okada, Eiji (Arrow Academy, 2019)
Winner of the Golden Leopard award at the 1970 Locarno Film Festival, "This Transient Life" is among the Art Theatre Guild s most successful and most controversial productions. The film concerns a brother and sister from a rich family who defy the expectations placed on them: he has little interest in further education or his father's business, instead obsessing over Buddhist statues; she continually refuses a string of suitors and the prospect of marriage. Their closeness, and isolation, gives way to an incestuous relationship which, in turn, breeds disaster. [Cover]
Keywords: Blu-Ray-Disc